Empoderamento feminino e a lógica da branquitude em influenciadoras digitais no Instagram - Toni, Gabriela Michelan de (Universidade Federal de São Carlos, 2025)
This work arises from questions raised by the way in which discourses involving the theme of female empowerment have been presented on digital social media. There is a dynamic in the dissemination of images of the female body associated with the agendas and discussions of the feminist movement. The problem in this context occurs because a considerable portion of the images present women's bodies that fit into a white hegemonic aesthetic standard and have a hypersensualized character. Thus, this research aims to analyze the way in which the idea of female empowerment and elements associated with this concept are presented on Instagram through the profiles oftwo digital influencers. For this, the profiles of Marcela McGowan (@marcelamcgowan) and Thelma Assis (@thelminha) are analyzed. Marcela (@marcelamcgowan) is a doctor, presenter, and digital influencer, while Thelma (@thelminha) is a doctor, dancer, presenter, YouTuber, and digital influencer. One of the main hypotheses is that the portrayal of the theme of "female empowerment," along with the elements associated with this concept, is situated within a context that values and disseminates aspects derived from white ideology and culture, here understood through the concept of whiteness. Preliminary results suggest that Instagram is a platform endowed with a set of practices and communicative tructures through which it influences and shapes the formation of individual subjectivities, assuming a pedagogical role. As for the dissemination of the idea of female empowerment associated with the perspective of whiteness, a diversity of interpretations has been diagnosed so far, requiring an approach capable of interpreting and assimilating the specific experiences of each group of women
Women's empowerment and the logic of whiteness in digital influencers on Instagram
Keywords: Empoderamento feminino; Branquitude; Influenciadoras digitais; Female empowerment; Whiteness; Digital influencers; CIENCIAS HUMANAS::EDUCACAO